Bilder zur Geschichte der Musik in Österreich. Von der Frühzeit bis 1600 - Salmen, Walter 1926-2013 (Helbling Innsbruck, 1979)
With this illustrated book, Walter Salmen presents for the first time a selection of more than 300 mostly previously unpublished pictorial documents on the history of music in Austria. The chronological span ranges from the 7th century B.C. to around 1900 and includes areas of sacred and secular art music practice as well as of usual music-making.
Keywords: Middle Ages (500-1400); 15th Century (1401-1500); 16th Century (1501-1600); Music history; Iconography; Austria